A precision medicine approach to management of acute myeloid leukemia in older adults. Issue 6 (November 2020) - Upadhyay Banskota, Shristi; Khanal, Nabin; Bhatt, Vijaya Raj
Abstract : Purpose of review: Therapy selection in older adults with acute myeloid leukemia (AML) can be challenging because of a higher incidence of high-risk cytogenetic and molecular features conferring chemoresistance and poor functional status leading to increased treatment-related toxicities. The purpose of this review is to highlight the recent advances in precision medicine in AML that have shown promise to improve outcomes of older adults. Recent findings: The utilization of next generation sequencing to identify and target actionable mutations can influence therapy selection in one-third of patients and can result in higher response rates as well as survival compared with those who do not receive targeted therapy. Oral targeted agents are available for AML with IDH 1, IDH2, or FLT3 mutations. Low-intensity venetoclax-based regimens have shown high rates of responses in AML, particularly among those with NPM1 and IDH2 mutations; responses are often durable and associated with minimal residual disease (MRD) negativity. Multiple studies have demonstrated the prognostic significance of flow cytometric MRD, with potential implications for subsequent therapy. Summary: Novel approaches for AML risk-stratification, MRD assessment, and a precision medicine approach offer significant promise to improve survival and quality of life of older adults.